Biogenic synthesis of Ag and AgO nanostructures for in vitro bactericidal applications: Influence of pH and physical reaction parameters on growth and properties of the nanostructures. (1st November 2022) - Gudipati, Tejovathi; Zaman, M Burhanuz; Kumari, Shubhlukshmi; Sharma, Monika; Pawaiya, Pragya Singh; Poolla, Rajaram
Abstract: In the present work Ag and AgO nanostructures were biogenically synthesized employing Tamarindus indica L fruit extracts that served as a reducing and capping agent. The influence of fruit aging (ripening) and the pH of the precursor solution on the growth and properties of the nanostructures was studied. The samples prepared under acidic condition contain predominantly monoclinic AgO along with traces of secondary phases (Ag2 O3 and Ag). Under alkaline conditions the material prepared is purely metallic silver exhibiting crystalline cubic phase. The extent of ripening and pH of the precursor solutions were found to have a direct influence on the crystallinity of the nanostructures. The metabolite content present in the extract was found to control the structure and morphology of the nanostructures. Isotropic growth is confirmed from the roughly spherical shape of the AgO nanoparticles having dimensions in the range 15–20 nm. Alkaline conditions cause supersaturation of the solutions resulting in the formation of nanostructures with diameter as small as 4–5 nm. The optical properties indicate occurrence of surface plasmon resonance (SPR) absorption at 335 nm for Ag nanoparticles. The AgO nanoparticles were explored for antimicrobial applications against the bacteria S. typhi and the nanoparticles exhibit good activity.